Odpowiedzi

  • Użytkownik Zadane
2009-10-25T14:07:49+01:00
A) √27-√18+√50-√200=
√(9*3)-√(9*2)+√(25*2)-√(100*2)=
3√3-3√2+5√2-10√2=
3√3-8√2
b) ∛3+∛24+∛54=∛3+∛(8*2)+∛(27*2)=∛3+2∛2+3∛2=∛3+5∛2
c)√12+√147÷√3 =√(4*3)+√(147:3)=√(4*3)+√49=2√3+7
2009-10-25T14:08:21+01:00
A) √27-√18+√50-√200=√(9*3)-√(9*2)+√(25*2)-√(100*2)=
3√3-3√2+5√2-10√2=3√3-8√2
b) ∛3+∛24+∛54=∛3+∛(8*2)+∛(27*2)=∛3+2∛2+3∛2=∛3+5∛2
c)√12+√147÷√3 =√(4*3)+√(147:3)=√(4*3)+√49=2√3+7
Najlepsza Odpowiedź!
2009-10-25T14:14:01+01:00
A) √27-√18+√50-√200=
√(9*3)-√(9*2)+√(25*2)-√(100*2)=
=3√3-3√2+5√2-10√2=
=3√3-8√2
b) ∛3+∛24+∛54=
=∛3+∛(8*2)+∛(27*2)=
=∛3+2∛2+3∛2=
=∛3+5∛2
c)√12+√147÷√3 =
=√(4*3)+√(147:3)=
=2√3+√49=
=2√3+7